Variations in anatomical landmarks of mandible using cone beam computed tomography - A cross-sectional study - Nitesh Tyagi; Neelkant Patil; Mohit Sareen; Manoj Meena; Supriya Rathore; Shobhit Kaswan (Wolters Kluwer Medknow Publications, 2021)
Background: Cone beam computed tomography (CBCT) is a diagnostic imaging modality for implant and surgical procedures in anterior and posterior mandibular area. It provides adequate information concerning maxillofacial regions, optimum image quality, excellent geometric accuracy, and low radiation dose. Aim: The aim of this study was to evaluate prevalence and anatomical variations in Mandible (Mandibular Incisive canal, Lingual Foramen, Mental Foramen, and Mandibular canal) in CBCT scans of the maxillofacial region. Methodology: All CBCT cross-sectional images of 40 study participants was analyzed for the presence of anatomical landmarks. All the anatomical parameters were compared with respect to age groups, dentition, gender, and right and left side and their respective distances from the inferior border of mandible and alveolar crest were measured using CS 3D imaging software (Kodak). Results: Lingual Foramen, Mental Foramen, and Mandibular Foramen were seen in all (100%) study samples, incisive foramen 83% and anterior loop in 25% of study samples. On statistical analysis, the difference of the mean distance of incisive foramen, mental foramen, anterior loop and mandibular foramen from lower border of mandible and alveolar crest was significant with relation to gender (P = 0.006) and with relation to dentate, partially dentate, and edentulous were found to be significantly different (P < 0.001). Conclusions: Careful assessment of the anatomical landmarks is essential to avoid neurosensory and bleeding complications using CBCT.